Utilization Chitosan Of Small Crab (Portunus Pelagicus) Shell Waste To Making Hand Body Cream - Santhy Wisuda Sidauruk; Dewita Buchari; Suardi Loekman (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
This research aimed was to evaluate the effect of chitosan on quality of hand body cream. Small crab shell was taken from crab canning processing plant (PT. Tonga Tiur Putra) Medan. The small crab shell was processed into powder; and the powder was extracted into chitosan. Four groups of hand body cream weighting 35 gram/each were prepared from a mixture of propilen glycol, triethanolamin, water, glyserin, lanolin, stearic acid and zaitun oil. The mixture then was added respectively with 1 ml of 0%, 1%, 2%, 3% of chitosan solution. Hand body cream quality were evaluated for humectan, viscosity, pH and emulsion stability. The result indicated that the humectan, viscosity, pH and emulsion stability of hand body cream were 55,74-66,6%; 21.653-48.747cPs; 6,84-7,37 and 61,33-64% respectively. Humectan and viscosity increased as the increasing of chitosan solution. However, pH decreased as the increasing of chitosan solution. There was no different effect of addition of chitosan solution on emulsion stability. Overall, addition of chitosan solution 3% resulted is superior quality of hand body cream with humectan, viscosity, pH and emulsion stability of 66,6%; 48.747cPs; 6,84 and 63% respectively.Keywords:Hand body cream, small crab shell, chitosan